2019
DOI: 10.1097/ccm.0000000000003842
|View full text |Cite
|
Sign up to set email alerts
|

XueBiJing Injection Versus Placebo for Critically Ill Patients With Severe Community-Acquired Pneumonia: A Randomized Controlled Trial

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 35 publications
0
126
0
Order By: Relevance
“…The recovery rate of SARS-CoV-2 infection is about 92.7% in China, and the mortality is 5.1% globally [6]. The virus is highly infectious, spreading rapidly in human-tohuman transmission, posing a dangerous threat to global public health [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery rate of SARS-CoV-2 infection is about 92.7% in China, and the mortality is 5.1% globally [6]. The virus is highly infectious, spreading rapidly in human-tohuman transmission, posing a dangerous threat to global public health [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The overall results of this large trial showed that XBJ is an effective and well-tolerated therapy for patients with severe CAP [14]. With high efficacy and good tolerability, XBJ compares favorably with the placebo.…”
Section: Discussionmentioning
confidence: 90%
“…Pharmacological studies have shown that XBJ has an antagonistic effect on endotoxin, and an inhibitory effect on the uncontrolled release of endogenous inflammatory mediators produced by endotoxin-stimulated monocytes/macrophages [11][12][13]. A recent well-done randomized study showed XBJ effective in patients with severe CAP [14]. Impressive benefit with this herbal-based medication was an 8.8% absolute reduction in mortality in patients who received XBJ.…”
Section: Introductionmentioning
confidence: 99%
“…For a long period of time in China, it was believed that XBJ could improve prognosis in severe lung infection [33] as well as 28-day mortality rate, Acute Physiologic Assessment and Chronic Health Evaluation (APACHE) II score, white blood cell (WBC) count, and temperature in sepsis patients without causing serious adverse events. A prospective, randomized controlled trial in 33 hospitals in China, published in September 2019, showed that XBJ can signi cantly improve the primary endpoint of pneumonia severity in patients with severe communityacquired pneumonia, as well as secondary endpoints such as mortality rate, mechanical-ventilation duration, and length of intensive-care unit (ICU) stay [34]. This study preliminarily demonstrated XBJ's "multiple component-multiple target-multiple pathway" effector characteristics, and our network topology analysis of potential effector targets identi ed some critical effector targets of the compound.…”
Section: Discussionmentioning
confidence: 99%